Software-Defined Networks for Optical Networks Using Flexible Orchestration: Advances, Challenges, and Opportunities - Nsafoa-Yeboah, Kenneth; Tchao, Eric Tutu; Yeboah-Akowuah, Bright; Kommey, Benjamin; Agbemenu, Andrew Selasi; Keelson, Eliel; Monirujjaman Khan, Mohammad (Journal of Computer Networks and Communications, 2022)
Optical networks offer a wide range of benefits to the telecommunication sector worldwide with their provision of higher bandwidth, which leads to faster data speed, longer transmission distance, and improved latency. Currently, the complexity associated with advancements in optical networks poses problems to network flexibility, reliability, and quality of service. Over the years, many reviews and proposals have been implemented by several literature studies to provide solutions for optical networks using software-defined networks and network service orchestrators. This study reviews the significant challenges in current optical network applications, the various solutions rendered by software-defined networks, and network service orchestration, impediments, and gaps in these software-defined networks. This study will go a step further to look into the various improvements and implementations of software-defined networks tailored to solve specific optical network problems. This study further proposes a flexible orchestration architecture for software-defined networks for solving flexibility and scalability problems in optical networks. This proposal uses an open network system (ONOS) SDN controller, leveraging on dockerisation and Kubernetes clusterisation and orchestration. This solution presents a more flexible, reliable, customable, and higher quality of service, which is an improvement upon current solutions in the literature.